Effectiveness of a mobile smoking cessation service in reaching smokers at workplaces - Mohamad Noor, Zaswiza; Nik Mohamed, Mohamad Haniki; Draman, Samsul; Md Aris, Mohd Aznan; Shaik Rahman Bux, Siti Halimah Bux; Abd Rahman, Norny Syafinaz (2009)
Background: Different smoking cessation programmes have been developed in the last decade, but developing new concepts are at important states. We established a mobile smoking cessation service to reach smokers at workplaces. With difficulties in getting smokers to attend quit smoking clinics in Malaysia, the existence of such service is vital. To our knowledge, this is the first mobile smoking cessation service ever established in our country. Objective: To assist and motivate smokers to quit and to provide pharmacotherapy whenever necessary. Method: Team consists of four pharmacists and two physicians. Service targeted smokers at workplaces (age 18 to 60). Trained professionals provided motivational talks, and free supply of pharmacotherapy when required. Follow up was arranged at 1 month by telephone, and at 3 and 6 months by face-to-face plus carbon monoxide test and urine cotinine validation. Records sheets were used for data collection. Result: 12 industries have participated since November 2007. 155 smokers received intensive smoking cessation service. By intention-to-treat, the prevalence quit rate was 14 % and 38% smoking less than 10 cigarettes at 1 month. 88% quit for health reasons while 67% quit for family. 85% had tried to quit before. 81% used self motivation, only 2% attended quit smoking clinic. Conclusion: Most smokers want to quit, but feel difficult to get help. Accessibility of mobile smoking cessation service is an advantage to assist smokers to quit.